France : Selected Issues Paper. (IMF Staff Country Reports; Country Report ;, 2010)
The staff report gives details of some selected issues of France, namely its credit developments, systematic linkages of French banks, the need for a significant fiscal consolidation for macroeconomic stability, an update on the developments of France's external competitiveness, and also the evolution of its export performance after the 2008 financial crisis. The report describes these issues in detail, and recommendations are also cited.